Academic Stress and Blood Glucose Levels: A Correlational Study Among Medical Laboratory Technology Students - Lisa Savitri; Mochamad Hanif Hilmi; Elfred Rinaldo Kasimo; Rochmad Krissanjaya; Kharisul Ihsan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels, often influenced by various physiological and psychological factors. One such factor is stress, particularly academic stress among university students. This study aims to explore the potential correlation between academic stress levels and random blood glucose levels among Medical Laboratory Technology (D.IV) students at Kadiri University. A cross-sectional, quantitative approach was used in this study. A total of 28 eligible students participated. Academic stress levels were assessed using the Perceived Sources of Academic Stress (PSAS) questionnaire, while random blood glucose levels were measured using spectrophotometric methods with glucose GOD FS reagents. Data were analyzed using the Pearson correlation test to determine the relationship between the two variables. The majority of students experienced moderate academic stress (71.43%), while the rest (28.57%) experienced high stress. No students reported low stress levels. Regarding blood glucose, 53.57% of participants had normal levels, and 46.43% had elevated levels. The Pearson correlation coefficient was 0.045 with a p-value of 0.819, indicating no statistically significant relationship between academic stress levels and blood glucose levels. Regression analysis also confirmed that while there was a slight positive trend (suggesting that higher stress may slightly raise glucose levels), the effect was negligible and not statistically significant. This study found no significant correlation between academic stress and random blood glucose levels among Medical Laboratory Technology students. Although stress may contribute to changes in glucose levels through hormonal mechanisms, other factors—such as diet, physical activity, and individual coping strategies—likely play a more substantial role. Interventions focusing on stress management, healthy lifestyle habits, and regular health monitoring are recommended to maintain both psychological well-being and metabolic health in students.